2022
DOI: 10.1097/01.jaa.0000823176.02964.c4
|View full text |Cite
|
Sign up to set email alerts
|

The PA profession in the 1990s

Abstract: The causes of events are ever more interesting than the events themselves."-Cicero

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 58 publications
(118 reference statements)
0
5
0
Order By: Relevance
“…When thinking about how commonly cited barriers affected their own work, most participants did not describe being affected the same way other faculty traditionally do. 1,2 Barriers were acknowledged, but participants transcended the obstacle. For example, all participants described time constraints but used effective organizational strategies to prioritize scholarship and make time for what they enjoyed.…”
Section: Discussion Professional Identify Formation Of the Scholarmentioning
confidence: 99%
See 2 more Smart Citations
“…When thinking about how commonly cited barriers affected their own work, most participants did not describe being affected the same way other faculty traditionally do. 1,2 Barriers were acknowledged, but participants transcended the obstacle. For example, all participants described time constraints but used effective organizational strategies to prioritize scholarship and make time for what they enjoyed.…”
Section: Discussion Professional Identify Formation Of the Scholarmentioning
confidence: 99%
“…However, the traditional role that faculty play in most academic disciplines in conducting research and performing scholarly work seems not to be a prominent feature of most PA programs. 1,2 It is well established that PA educators do not publish or produce scholarship at the same rate as peer educators in nursing, medicine, or other health professions. 3,4 Research has shown that the vast majority of PA faculty have not produced a scholarly publication in their academic career 3,4 regardless of the number of years as faculty.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was a grim realization for the young PA profession already struggling with state legislative challenges and acceptance, and resulted in defections from the profession, a decline in applications, and the closure of a number of PA programs. 7 Closures included the PA programs at Johns Hopkins University (1979), Indiana University (1981), and Penn State University (1984). All three of these institutions have reestablished their sponsorship of PA educational programs.…”
Section: The Effect Of Gmenacmentioning
confidence: 99%
“…Many of those who readily accepted the prediction of a physician surplus asked: If we will have too many physicians, why do we need PAs? This was a grim realization for the young PA profession already struggling with state legislative challenges and acceptance, and resulted in defections from the profession, a decline in applications, and the closure of a number of PA programs 7. Closures included the PA programs at Johns Hopkins University (1979), Indiana University (1981), and Penn State University (1984).…”
Section: The Effect Of Gmenacmentioning
confidence: 99%